(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the collaborative dynamics between dentists and dental assistants in delivering comprehensive patient care within the dental practice. Key aspects of their roles, including patient intake, treatment planning, chairside assistance, and patient education, are examined to elucidate the teamwork essential for optimal outcomes. Effective communication and coordination strategies are emphasized as foundational elements facilitating seamless workflow and patient safety. Additionally, the significance of building trust and rapport with patients is underscored, highlighting its impact on treatment adherence and patient satisfaction. Furthermore, the importance of continuing education and professional development for both dentists and assistants is discussed, emphasizing the need for ongoing skill enhancement to meet evolving patient needs. Overall, this article illuminates the collaborative synergy between dentists and dental assistants, underscoring their shared commitment to providing exemplary dental care.